Aplikasi Serat Serabut Kelapa Bermatrik Sagu dan Gliserol Sebagai Pengganti Kemasan Makanan Dari Sterofoam - Bahtiar, Ahmad Dony Mutiara (Jurnal Teknik Mesin (JTM), 2012)
This research focuses on biocomposite material which is applied for food packaging to substitute polystyrene packaging. The purpose of this research is to know the influence of coconut fiber towards biocomposite streng tensil  with sago palm matrix and glycerol.  Sago palm and glycerol is matrixes coming from biocomposite and coconut fiber as the filler. This research is using volume glycerol fraction and sago palm, with sago palm as 10% plastisiser since the volume fraction has the most optimum for 1.395v Mps and 70% glatinasi temperature, wherein volume biocomposite fraction is 45% coconut fiber, 105 glycerol, and 45% sago palm has the optimum steng tensil of 4.744 Mpa. In comparison when volume fraction is 75% of coconut fiber, 10% of glycerol and 15% of sago palm, it makes the lowest average of kekuatan tarik of 1.187 MPa. Therefore, bicomposite with sago palm matrix, glycerol, and coconut fiber still has bigger compared to polyesterene steng tensil which is occasionally used for food packaging having 3.27 MPa.